Economic consequences of healthcare optimization for IBD patients in the Republic of Tatarstan - T. P. Bezdenezhnykh; D. V. Fedyaev; G. R. Khachatryan; G. G. Arutyunov; K. V. Gerasimova (IRBIS LLC, 2019)
The integrated Model of health care for patients with inflammatory bowel disease (IBD) is based on the creation of specialized centers where multidisciplinary teams provide patient-centered care. Recent studies showed that the introduction of such approach into the IBD treatment practice led to faster diagnosis, an increase in the proportion of patients with mild forms of IBD and, as a result, the reduction of medical costs. The present study aims to assess the economic consequences of the proposed IBD healthcare optimization in the Republic of Tatarstan. Materials and methods. A budget impact model was created to compare two scenarios: the basic case when IBD patients are treated according to the current practice based on the existing network of clinics versus the simulated scenario when IBD patients receive medical care within a specialized IBD center, organised in accordance with the integrated multidisciplinary approach. The study hypothesis implies that the proportion of patients with severe IBD is gradually decreasing due to the change in the treatment model and the improved diagnostic procedure. The direct medical costs included the cost of visits to doctors, ambulance calls, diagnostic tests, outpatient medications, and the day-time and 24-hour in-patient care. One-way sensitivity analysis of all model inputs was performed. Results. As a result of the modified practice in the Republic of Tatarstan, the cost of medical care for IBD patients will decrease by 120 million rubles over 5 years. The sensitivity analysis shows the results are robust and not sensitive to fluctuations in the variables. However, the results are shown to be most sensitive to fluctuations in the distribution of patients by IBD severity. Conclusion. The introduction of the integrated healthcare for patients with IBD will result in lower costs of this service.